Randomized phase II study of the Bruton tyrosine kinase inhibitor acalabrutinib, alone or with pembrolizumab in patients with advanced pancreatic cancer. Issue 1 (28th February 2020) - Overman, Michael; Javle, Milind; Davis, Richard E; Vats, Pankaj; Kumar-Sinha, Chandan; Xiao, Lianchun; Mettu, Niharika B; Parra, Edwin R; Benson, Al B; Lopez, Charles D; Munugalavadla, Veerendra; Patel, Priti; et al.
Abstract : Background: The immunosuppressive desmoplastic stroma of pancreatic cancer represents a major hurdle to developing an effective immune response. Preclinical studies in pancreatic cancer have demonstrated promising anti-tumor activity with Bruton tyrosine kinase (BTK) inhibition combined with programmed cell death receptor-1 (PD-1) blockade. Methods: This was a phase II, multicenter, open-label, randomized (1:1) clinical trial evaluating the BTK inhibitor acalabrutinib, alone (monotherapy) or in combination with the anti-PD-1 antibody pembrolizumab (combination therapy). Eligible patients were adults with histologically confirmed metastatic or locally advanced unresectable pancreatic ductal adenocarcinoma with an Eastern Cooperative Oncology Group Performance Status (ECOG PS) ≤1 who had received at least one prior systemic therapy. Oral acalabrutinib 100 mg twice daily was administered with or without intravenous pembrolizumab 200 mg on day 1 of each 3-week cycle. Peripheral blood was analyzed for changes in immune markers, and tumors from exceptional responders were molecularly analyzed. Results: A total of 77 patients were enrolled (37 monotherapy; 40 combination therapy) with a median age of 64 years; 77% had an ECOG PS of 1. The median number of prior therapies was 3 (range 1–6). Grade 3–4 treatment-related adverse events were seen in 14.3% of patients in the monotherapy arm and 15.8% of those in the combination therapy arm. The overall response rate and disease control rate were 0% and 14.3% with monotherapy and 7.9% and 21.1% with combination therapy, respectively. Median progression-free survival was 1.4 months in both arms. Peripheral blood flow analysis demonstrated consistent reductions in granulocytic (CD15+) myeloid-derived suppressor cells (MDSCs) over time. Two exceptional responders were found to be microsatellite stable with low tumor mutation burden, low neoantigen load and no defects in the homologous DNA repair pathway. Conclusions: The combination of acalabrutinib and pembrolizumab was well tolerated, but limited clinical activity was seen with either acalabrutinib monotherapy or combination therapy. Peripheral reductions in MDSCs were seen. Efforts to understand and target the pancreatic tumor microenvironment should continue. Trial registration number: NCT02362048 .